2014
DOI: 10.22146/ijcn.18867
|View full text |Cite
|
Sign up to set email alerts
|

Sanitasi, infeksi, dan status gizi anak balita di Kecamatan Tenggarong Kabupaten Kutai Kartanegara

Abstract: Background: Malnutrition is a public health problem commonly encountered in developing countries. Almost 50% of 10-11 millions of mortality among children under-fives caused by malnutrition that is preventable. District of Kutai Kartanegara is known as the most wealth of district in Indonesia, yet the wealth cannot automatically solve the problem of its people. Numerous efforts have been made to solve malnutrition problem yet the morbidity rate is still relatively high.Objective: The study aimed to identify an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
1
5
0
6
Order By: Relevance
“…Moreover, this study found that mothers with poor knowledge about drinking safe and sufficient water will also have a greater risk of malnutrition in her toddlers than mothers who are well informed about drinking enough and safe water. It is in line with Abeng et al, (2014) and Hidayat & Fuada (2011), that poor sanitation will make children more susceptible to infectious diseases which may ultimately affect nutritional status. Environment sanitation is also strongly associated with the availability of clean water, availability of toilet, etc.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Moreover, this study found that mothers with poor knowledge about drinking safe and sufficient water will also have a greater risk of malnutrition in her toddlers than mothers who are well informed about drinking enough and safe water. It is in line with Abeng et al, (2014) and Hidayat & Fuada (2011), that poor sanitation will make children more susceptible to infectious diseases which may ultimately affect nutritional status. Environment sanitation is also strongly associated with the availability of clean water, availability of toilet, etc.…”
Section: Resultssupporting
confidence: 54%
“…Environment sanitation is also strongly associated with the availability of clean water, availability of toilet, etc. The more available clean water for daily needs, the less risk of malnutrition for children (Abeng et al, 2014) (Hidayat & Fuada, 2011). However, this study was in contrast to Puspitawati who found that sanitation (clean water availability) has no association with children nutrition's status (Natalia & Tri, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Balita yang mengalami ISPA berpeluang 5,32 kali mengalami wasting. 15 ISPA merupakan salah satu penyakit infeksi yang erat kaitannya dengan masalah gizi. Tanda dan gejala penyakit ISPA ini bermacam-macam antara lain batuk, kesulitan bernafas, tenggorakan kering, pilek, demam dan sakit telinga.…”
Section: Hasil Penelitianunclassified
“…The emergence of malnutrition is not only due to lack of food but also because of disease. Children who get enough food may get diarrhea or fever, which leads to malnutrition [8]. Likewise, in children who do not eat well enough, their immune system can be weak.…”
Section: Acceptabilitymentioning
confidence: 99%